Fine structure of the diatoms Thalassiosira and Coscinodiscus (Bacillariophyceae) : Light and electron microscopy observation - Fareha, Hilaluddin; Chui, P.L; Po, T.L (Annals of Microscopy, 2010)
A study was carried out to examine the morphology of diatom species in Sarawak, Malaysia. Plankton sampling was conducted using 20 μm mesh-size plankton net at two estuaries in Kuching, Sarawak, Malaysia; Santubong and Samariang Batu. Plankton samples were brought back to the laboratory and treated with acid wash before detailed observation under the light and electron microscopes. All samples were identified to species level based on the transmission and scanning electron microscope (TEM and SEM).